Pengaruh Disiplin Kerja dan Komitmen Kerja terhadap Prestasi Kerja Karyawan pada PT. Bintang Toedjoe Kota Kediri - Dadang Wahyu Asmoro; Nur Laely; Budi Rahayu (Politeknik Raflesia Press, 2026)
This research aims to determine the simultaneous influence of work discipline and work commitment on employee performance at PT. Bintang Toedjoe, Kediri City. This research employs a quantitative research method as the research data is in numerical form and is analyzed using statistics, adhering to scientific principles such as being concrete, objective, measurable, rational, and systematic. The population in this study is all employees at PT. Bintang Toedjoe, Kediri City, totaling 340 people. The sample in this study consists of 77 respondents. The sample size was determined using the Slovin formula. Data collection methods include observation, documentation, and questionnaires. Data analysis methods used include descriptive percentage analysis, classical assumption testing, and multiple linear regression analysis, simultaneous significance test (F test), t-test (partial), and coefficient of determination (R2) test. The results of this study conclude that: (1) There is a partial influence of work discipline on employee performance at PT. Bintang Toedjoe, Kediri City. (2) There is a partial influence of work commitment on employee performance at PT. Bintang Toedjoe, Kediri City. (3) There is a simultaneous influence of work discipline and work commitment on employee performance at PT. Bintang Toedjoe, Kediri City of 65%, while the remaining 35% is influenced by other factors not examined in this study